1982
DOI: 10.1007/bf01055182
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and biotransformation of benzo(a)pyrene inChironomus riparius

Abstract: Uptake and depuration kinetics for benzo(a)pyrene (B(a)P) were determined for the midge Chironomus riparius (Diptera) with one and two compartment models. Nonfeeding animals were exposed to nominal 1.0 microgram.L-1 14C- B(a)P for eight hr. Depuration over eight hr was determined in animals with and without substrate. The uptake rate constant was 214 +/- 20 hr-1 (X +/- SE, n = 3), while elimination rate constants for the first four hr were 0.22 hr-1 (with substrate) and 0.06 hr-1 (without substrate). Biphasic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…Simultaneous estimation of rate constants from consecutive exposure and elimination studies has been used only by a limited number of authors for the one-compartment model (34). For two-compartment model studies (30,(35)(36) such an approach has not yet been used. The recent availability of user-friendly computer programs with numerical techniques for the solution of the differential equations enables simultaneous parameter estimation for compartment models even with time-variable water concentrations (23,(37)(38).…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneous estimation of rate constants from consecutive exposure and elimination studies has been used only by a limited number of authors for the one-compartment model (34). For two-compartment model studies (30,(35)(36) such an approach has not yet been used. The recent availability of user-friendly computer programs with numerical techniques for the solution of the differential equations enables simultaneous parameter estimation for compartment models even with time-variable water concentrations (23,(37)(38).…”
Section: Methodsmentioning
confidence: 99%
“…Steady state is driven not only by thermodynamics but also by active metabolic processes. These metabolic processes, such as reductions due to biotransformation [23] and elevations due to active ingestion [24], can result in steady-state accumulations substantially different from those predicted by thermodynamic equilibrium. Additionally, toxicant concentrations in the field can vary manyfold over time, violating the assumption of a steady-state exposure.…”
Section: Steady-state Modelsmentioning
confidence: 96%
“…Biotransformation can alter the toxicant distribution among the various tissues of an organism [81,82] and will alter any estimate of the elimination rate or BCF measured with total radiotracer unless biotransformation losses are considered [23,. If k, is derived from measurement of the parent compound, it will include both the elimination of the parent toxicant and its metabolism.…”
Section: Environmental and Physiological Factorsmentioning
confidence: 99%
“…The bioavailability of sediment-sorbed and ingested BA contrasts with an earlier report by Rossi (1977) who found PAR in these forms unavailable for uptake by the worm Neanthes arenaceodentata. Other investigations with worms have reported PAR and PCB accumulation from sediment and dietary sources (Augenfeld et al, 1982;Lyes et al, 1979;Courtney and Langston, 1978;Goerke, 1979;Roesijadi et al, 1978;Fowler et al, 1978); as have investigations with other organisms such as fish Gmur, 1981, Varanasi et aI., 1979;Palmork and Solbakken, 1981), midge larvae (Leversee et al, 1982), blue crab larvae (Lee et a1., 1976), and the accumulation of PCBs in larval bivalves (Dobroski and Epifanio, 1980).…”
Section: Discussionmentioning
confidence: 88%
“…Boehm and Quinn (1973) found that dissolved organic matter (DOM) increased the solubility of hydrocarbons in seawater, and that removal of DOM increased accumulation of hydrocarbons by filter feeding bivalves (Boehm and Quinn, 1976). Leversee et al (1982) reported that accumulation of several PAR by Daphnia were affected by the presence of synthetic (Aldrich humic acids) or natural DOM, or natural particulate matter. Particulate size and organic content are also known to influence feeding behavior of benthic organisms.…”
mentioning
confidence: 99%